Caracterização químico-estrutural, propriedades reológicas e atividades biológicas do polissacarídeo hidrolisado e sulfatado da alga Gracilaria intermedia - Costa, Luís Eduardo Castanheira (2020)
The sulfated polysaccharide of the red seaweed Gracilaria intermedia (PGi) was extracted by enzymatic hydrolysis and subjected to hydrolysis and chemical sulfation changes. These polysaccharides were submitted to chemical composition tests, and PGi showed with low sulfate substitution and high molar mass. Hydrolysis was able to reduce the molar mass and structural characterization by HSQC nuclear magnetic resonance revealed that PGi is a sulfated agaran with pyruvic acid substituent groups. Rheological behavior was evaluated using different PGi concentrations. The predominantly viscous response and pseudoplastic rheological behavior of the sulphated polysaccharide extracted from Gracilaria intermedia suggests a potential use of this polymer as a thickening agent. The effect of native, sulphated and hydrolyzed polysaccharide in coagulation is was evaluated through activated partial thromboplastin time (ATTP) and prothrombin time (TP) tests, where PGi, HPGi and SPG have the same level of impact on the intrinsic. coagulation cascade. The in vitro antioxidant activity of polysaccharides was also tested for total antioxidant capacity, radical hydroxyl scavenging and ferrous ion chelation. The best activity in total antioxidant capacity was achieved at a concentration of 4 mg/mL for all polysaccharide forms, showing a good antioxidant activity and a potential to be used in food industry, besides being a substitute for toxic compounds like BHT and BHA. PGi toxicity was also evaluated through the MTT test, where the polysaccharide proved not to be toxic in the concentrations used. The wound healing activity of a gel composed of PGi and galactomannan extracted from Caesalpinia pulcherrima in the clean wound model in mice was also evaluated. The formed gel (G '> G ") exhibits elastic characteristics at different temperatures and the behavior of a weak gel and in the wound healing test, the gel shows the ability to accelerate healing within three to seven days of treatment.